Analysis of surface-emitting thin-film superluminescent diodes with high efficiency - Jentzsch, Bruno; Gomez-Iglesias, Alvaro; Tonkikh, Alexander; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
In this paper, a novel surface-emitting superluminescent diode fabricated by applying full on-wafer processing is presented. The surface-emission is achieved via mirrors etched by using an inductively coupled plasma process. This geometry allows to deflect in-plane guided and amplified optical modes perpendicular to the chip surface. The out-coupling window is anti-reflection coated, while at the other end of the waveguide a high-reflecting coating was deposited. In this way the device uses double-pass amplification, increasing efficiency, and light is emitted from a single spot. The light propagation and out-coupling in the proposed concept are first theoretically analyzed. Moreover, in order to simulate the optical output power, a rate equation-based frequency-resolved model accounting for non-ideal facet reflectivities and lasing onset is introduced. Finally, the measured L-I and spectral characteristics of fabricated InGaAs/GaAs superluminescent diodes emitting at a peak wavelength of 960nm are presented and compared to simulation results. At room temperature, pulsed output powers up to ∼125mW with a FWHM of 14nm and a wall-plug efficiency higher than 10% were achieved.
CRIS-Team Scopus Importer:2021-06-11
Keywords: SLED; Superluminescent Diode; Surface-Emission; Thin Film Technology